ARM PROCESSOR BASED COLLISION AVOIDANCE AND BLIND SPOT DETECTION TECHNIQUES - Amar Birajdar, Sanket Thalkari, Shrikant Kumbhar (International Journal of Research Science and Management, 2015)
This paper presents ultrasonic and infrared sensor based distance measurement techniques for automotive applications, to avoid the collision and detection of blind spot. Ultrasonic sensors are well-accepted technology for distance sensing applications, they provides accurate distance measurement. Infrared sensors are also included to detect the presence or absence of object. This system provides alert to driver when object/ vehicles have detected, which is closer to predefined level and also necessary action will be taken to avoid collision. ARM Nuvotn processor is used in this design to perform complex task with effective distance sensing as well as provides alert to the driver. This is low cost design intended for automobile safety to avoid collisions the proposed systems detect blind spots areas and it avoids collisions. The feasibility of this approach and its robustness against environmental conditions are tested by means of various experimental testings performance.